La teología islámica de la liberación desde shadaab rahemtulla frente la tradición islámica (2021)
This article analyzes the Islamic liberation theology against Islamic traditionalism from the various reflections of the Indian academic Shadaab Rahemtulla. Rahemtulla's main thesis lies in postulating the reading of the Koranic surhas as a liberating action, that is, without rigid political or social ties. This in order to achieve a true emancipation from all those conditions that have made it impossible for many Islamic countries to have significant projects aimed at improving the indeces of social equity, political participation and freedom of expression. Therefore, the methods of interpretation of the sacred text are analyzed, in addition to the hegemonic practices that the traditional discourse has implemented in order to preserve the status quo.